Student’s Statistical Literacy Skills (1980-2023): A Systematic Literature Review with Bibliometric Analysis - Febrinna Marchy; Dadang Juandi (Department of Mathematics Education, Faculty of Teacher Training and Education, Wisnuwardhana University of Malang, 2023)
There have been demands to enhance the statistical literacy in the mathematics curriculum due to the vital role statistics plays in both everyday life and professional environments.The main purpose of this research is to investigate the heterogeneity and research landscape pertaining to students' statistical literacy skills.This research employs a systematic literature review approach combined with bibliometric analysis as the chosen methodology. Data obtained from the Scopus database which has been refined through the PRISM method. The results show that the publication trend has increased in recent years. Publications in 2017 had the most impact in this area. The United States of America is the most influential country in this study. Most of the research was conducted at the secondary school level and most were published in Q3 journals. The learning method most often used in research related to students' statistical literacy skills is project based learning. Information on research developments related to students' statistical literacy skills can serve as a valuable reference for future researchers. It is strongly advised for educators and researchers to conduct further investigations into the statistical literacy skills of students in Asia and Africa, particularly focusing on the primary school level.